2023
DOI: 10.1101/2023.03.06.531278
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morphine Re-arranges Chromatin Spatial Architecture of Primate Cortical Neurons

Abstract: The expression of linear DNA sequences are precisely regulated by the three-dimensional (3D) architecture of chromatin. Morphine-induced aberrant gene networks of neurons have been extensively investigated; however, how morphine impacts the 3D genomic architecture of neurons is still unknown. Here, we applied digestion-ligation-only high-throughput chromosome conformation capture (DLO Hi-C) technology to investigate the affection of morphine on the 3D chromatin architecture of primate cortical neurons. After r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…Recent studies have begun to shed light on the intricate relationship between 3D chromatin architecture and gene expression under various conditions. For instance, research on primate cortical neurons exposed to morphine showed rearrangement in chromosome territories and alterations in TADs, which were associated with changes in gene expression (48). In the pursuit of deciphering 3D chromatin architecture, methodologies such as chromosome conformation capture (3C) and its derivative Hi-C, as well as techniques like DNA-FISH, have been instrumental.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have begun to shed light on the intricate relationship between 3D chromatin architecture and gene expression under various conditions. For instance, research on primate cortical neurons exposed to morphine showed rearrangement in chromosome territories and alterations in TADs, which were associated with changes in gene expression (48). In the pursuit of deciphering 3D chromatin architecture, methodologies such as chromosome conformation capture (3C) and its derivative Hi-C, as well as techniques like DNA-FISH, have been instrumental.…”
Section: Discussionmentioning
confidence: 99%